Heart Rate And Blood Pressure In Soccer Players Differing In Sports Qualification - Mykhaliuk, Ye. L.; Horokhovskyi, Ye.; Bosenko, A.; Bazylchuk, O.; Khoroshukha, M.; Orlyk, N.; Topchii, M.; Михалюк, Євген Леонідович (My University, 2024)
Aim: To investigate the effects of exercise training on heart rate and blood pressure in soccer players of different skill levels. Materials and Methods: 693 soccer players with different sports qualifications were studied. Heart rate (HR) and blood pressure (BP) were measured at rest at the beginning of the preparatory phase of the training cycle. Results: HR in elite soccer players is 64.4±0.83 bpm, bradycardia occurs in 47.4%, tachycardia in 5.3%, hypotonic state of systolic (SBP) and diastolic (DBP) blood pressure in 9.0% and 8.3%, hypertensive state of SBP and DBP in 41.4% and 17.3%, respectively. HR in advanced soccer players is 67.5±0.5 bpm, bradycardia occurs in 36.0%, tachycardia in 8.6%, hypotonic state of SBP and DBP occurs in 11.1% and 32.9%, hypotonic state of DBP in 9.1%, and hypertensive state of DBP in 13.7%. The HR in intermediate soccer players is 71.3±0.73 bpm. Players with bradycardia in this group were found 21.3%, and with tachycardia 17.8%. Hypotonic state of SBP was found in 17.2% of players, and hypertonic state in 19.0%. Hypotonic state of DBP was found in 19.5% and hypertensive state in 8.6% of players. Bradycardia and hypertensive state of SBP are significantly more frequent in elite players than in intermediate players. Conclusions: Considering the presence of 12.9% of athletes with BP ≥ 140/90 mmHg among advanced soccer players, it is recommended to perform additional examinations, including daily BP monitoring, as well as to make adjustments in the training and rehabilitation process.
Keywords: soccer players; sports qualification; bradycardia; tachycardia; hypotonic and hypertensive states